Exploration of the development challenges that are faced by the residents of informal settlements near railway lines: the case of Dukathole informal settlement. - Mmonwa, Sylvester Folae (My University, 2008)
ABSTRACT As a result of vacant and unregulated land close to railway lines, poor people tend to build their informal structures in such areas, thus putting their health and well being at risk, for instance the danger of being ran over by trains. Such occupation also threatens to disrupt the railway services. This problem is not unique to South Africa and in this study I draw on cases from India and Kenya. These countries wre identified, because they have set precedence in informal settlement upgrading and their experience can guide the policy formulation process in South Africa. This study explores the development challenges that are faced By informal settlers on railway reserves, using a case study of Dukathole informal settlement in Ekurhuleni Metropolitan Municipality (EMM). During the investigation it was found that the interviewees at Dukathole informal settlement are not able to participate in the process of dealing with their own development challenges and are not aware of any development planning taking place for Dukathole, although such planning is underway. This is in contrary to the way in which informal settlers are treated in the case studies fo India and Kenya, where they are regared as active role players in addressing their own development challenges.